Psychometric Validation of the Multidimensional Scale of Perceived Social Support During Pregnancy in Rural Pakistan - Sharif, Maria; Zaidi, Ahmed; Waqas, Ahmed; Malik, Abid; Hagaman, Ashley; Maselko, Joanna; LeMasters, Katherine; Liaqat, Rakhshanda; Bilal, Samina; Bibi, Tayyaba; Ahmad, Ikhlaq; Sikander, Siham; et al. (Frontiers in Psychology, 2021)
Background: The Multidimensional Scale of Social Support (MSPSS) is a short and reliable instrument that assesses perceived social support from ones’ social network. A previous study in Pakistan among postpartum women has demonstrated a uni-dimensional factor structure, in contrast to the original three-factor structure. The emergence of a one-factor structure for postpartum women in Pakistan may be due to traditional postpartum practices unique to the women of the subcontinent. Building upon the previous evidence, this study aims to explore the psychometric properties of MSPSS among pregnant women in their third trimester in rural Pakistan. Methods: A cross-sectional survey was conducted from Oct 2014 to Feb 2016, in rural Pakistan. A sample of 1,154 pregnant women (aged > 18 years) in their third trimester and registered with local lady health worker program, living in the north of the Punjab Province were included in this study. They were assessed using Urdu translated scales of Patient Health Questionnaire, MSPSS, Maternal Social Support Index, and Perceived Stress Scale. Principal Axis Factoring was used to assess the construct validity of the MSPSS. Results: The MSPSS scale showed an excellent internal consistency, yielding a Cronbach’s alpha value of 0.933. MSPSS scale exhibited excellent construct validity and confirmatory factor analysis retained three factors (family, friends and significant others) for both the depressed and non-depressed samples. Internal reliability and construct validity were also established. Conclusion: The psychometric findings suggest that the tridimensional structure of MSPSS is a valid and reliable measure of perceived social support among the Pakistani population with and without perinatal depression. Perceived social support is an important predictor of maternal mental wellbeing and psychopathologies, and the MSPSS can serve as a useful tool in mental health research in Pakistan.